PENGARUH PENGGUNAAN LKPD BERORIENTASI TAKSONOMI BLOOM REVISI DALAM SETTING PENDEKATAN SAINTIFIK TERHADAP PENCAPAIAN KOMPETENSI FISIKA PESERTA DIDIK KELAS X SMA NEGERI 7 PADANG - Reysa Humaira; Amali Putra; Syafriani Syafriani (Universitas Negeri Padang, 2017)
The physic competence achievement of SMA Negeri 7 Padang students still does not meet the expectation. The use of LKPD oriented on Bloom’s taxonomy revision with the implementation of scientific approach is believed to be effective to reach the expected physic competence of the students. This research is aimed to analyze the effect of using LKPD oriented on Bloom’s taxonomy revision with the implementation of scientific approach setting toward physic competence achievement of grade X students of SMA Negeri 7 Padang.Type of research is quasi experiment with Posttest Only Control Group Design. The study population was all students of class X MIA at SMAN 7 Padang enrolled in the Academic Year 2016/2017. Sampling was done by cluster sampling technique. Samples were class X MIA 1 as the control class and class X MIA 4 as an experimental class with a number of sample members of each class is 31 people. This research data includes data competence of attitudes, knowledge, and skills. Data were analyzed using the equality test two averages (t test), simple linear regression and correlation tests on the real level of 0.05 to the competence of knowledge, using the equality test two averages (t test) for competency skills, attitude and competencies using trend graphs change in attitude.The results of data analysis the average attainment of experimental class attitude at 79.15 is higher than the average grade of control that is equal to 77.2. On average the attainment of knowledge of the experimental class of 79 is higher than the average grade control is 75. The average achievement experimental class skill competencies of 83.3 is higher than the average grade of control that is 77.5. The test results of data analysis concluded that the LKPD oriented on Bloom’s taxonomy revision in setting the scientific approach can improve the competence of Physics students of class X SMAN 7 Padang. Great influence exerted LKPD oriented on Bloom’s taxonomy revision to the attainment of knowledge of students by 72.25%.